Impediments of rating revaluation: evidence from West Malaysian local authorities / Nor Azalina Yusnita Abd Rahman ... [et al.] - Abd Rahman, Nor Azalina Yusnita; Senawi, Asma; Mohamed Saraf, Mohamad Haizam; Che Pin, Siti Fairuz (2021)
Rating is a form of taxation payable by real estate owners on their holdings because of their ownership or possession on the property. A revaluation of all holdings is done once every 5 years or within such extended period as determined by the state government. The Ministry of Housing and Local Government has recorded that most of the local authorities haven't revalued the property for almost 35 years. Thus, a focus group interview was conducted to identify the impediments in a revaluation of rating among local authorities. The sample consists of 43 officers from 22 local authorities in west Malaysia. Finding from the focus group revealed 4 main issues; namely, (1) lack of knowledge in rating revaluation paperwork, (2) lack of manpower, (3) cost constraints, and (4) time-consuming.